β2‐adrenergic stimulation induces interleukin‐6 by increasing Arid5a, a stabilizer of mRNA, through cAMP/PKA/CREB pathway in cardiac fibroblasts - Shota Tanaka; Atsuki Imaeda; Kotaro Matsumoto; Makiko Maeda; Masanori Obana; Yasushi Fujio (Wiley, 2020)
Abstract Background and Purpose In cardiovascular diseases, cardiac fibroblasts (CFs) participate in the myocardial inflammation by producing pro‐inflammatory cytokines, worsening the prognosis. β2‐adrenergic receptor (AR) and β3AR are expressed in CFs, and β‐adrenergic stimulation promotes CFs to produce pro‐inflammatory cytokines. However, the mechanism of the expression of pro‐inflammatory cytokines in response to β‐adrenergic stimulation remains to be fully elucidated. Experimental Approach CFs were isolated from adult wild‐type or AT‐rich interactive domain‐containing protein 5A (Arid5a) knockout mice. The expression of mRNA was measured by real‐time RT‐PCR. Interleukin (IL)‐6 protein was measured by ELISA. The activity of nuclear factor‐κB (NF‐κB) and cyclic AMP (cAMP) response element binding protein (CREB) was assessed by ELISA‐like assay or Western blotting. Key Results The β‐adrenergic stimulation remarkably induced IL‐6 mRNA and protein through β2AR in CFs. The activation of adenylate cyclase and the enhancement of intracellular cAMP resulted in the upregulation of IL‐6 mRNA expression. The induction of IL‐6 transcript by β2AR signaling was independent of NF‐κB. Concomitant with IL‐6, the expression of Arid5a, an IL‐6 mRNA stabilizing factor, was enhanced by β2‐adrenergic stimulation and by cAMP increase. Importantly, β2AR signaling‐mediated IL‐6 induction was suppressed in Arid5a knockout CFs. Finally, β2AR stimulation phosphorylated CREB via PKA pathway, and the activation of CREB was essential for the induction of Arid5a and IL‐6 mRNA. Conclusion and Implications β2‐adrenergic stimulation post‐transcriptionally upregulates the expression of IL‐6 by the induction of Arid5a through cAMP/PKA/CREB pathway in adult CFs. β2AR/Arid5a/IL‐6 axis could be a therapeutic target against cardiac inflammation.